LITERARY LITERACY: TEACH OR MEDIATE READING? - Eduardo Braga, Carlos (Revista Gênero e Interdisciplinaridade, 2024)
The work entitled "Literary Literacy: Teaching or Mediating Reading?" Carlos Eduardo Braga explores the importance of literary literacy in the educational context. The research addresses the dichotomy between direct teaching and the mediation of reading, investigating which approach is most effective in the formation of critical and proficient readers. The study highlights the relevance of literary literacy for the cognitive, emotional and social development of students, and proposes an analysis of pedagogical practices that can promote a more engaged and autonomous reading environment. The methodology used is bibliographic research, with literature review of renowned authors in the area.